PENGARUH DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN E-COMMERCE SHOPEE DI KOTA SORONG - Susana Magdalena Welly Muskita; Ratna Rosmauli Pakpahan; Arce Yulita Ferdinandus (JURNAL BADATI, 2025)
In today's digital age, technological advances have become an integral part of human life. Along with changes in lifestyle and consumer purchasing behavior, people who used to prefer buying goods directly from markets or stores now prefer to buy online or from marketplace stores. Shopee is one of the leading e-commerce platforms that provides online buying and selling services. Shopee offers a variety of products, ranging from electronics, fashion, daily necessities, and others. The purpose of this study is to determine the effect of digital marketing on the purchasing decisions of e-commerce consumers in Sorong. The method used is quantitative. The results of this study are as follows: The partial test (t-test) results show that t – the calculated value of 7.235 > the t- table value of 1.673, where the partial test calculation yielded a significance value of 0.000 at a 5% significance level, where 0.000 < 0.05, meaning the hypothesis is accepted, indicating that digital marketing partially influences e-commerce purchasing decisions. The result of the coefficient of determination (R square) is 0.488 (48.8%), while the remaining 51.2% (100%–48.8%) is influenced by other variables not included in the research model.